Cagoule noire et ongles roses : féminismes et rapports de pouvoir dans la gauche radicale de Göttingen - Fourment, Emeline (Institut d'études politiques de Paris, 2014)
Keywords: 2000 à aujourd'hui; 2010-2019; allemagne; approches et analyses; discipline; ethnographie; europe; göttingen; militance; mémoires/thèses; périodes historiques; queer; régions géographiques; science politique; science politique et droit; thématiques

Law Reform, Lesbian Parenting, and the Reflective Claim - Leckey, Robert (Social & Legal Studies, 2011)
The article aims to complicate efforts to make law fit or catch up to social practices. It scrutinizes the ‘reflective claim’ using the case study of recognition of parenting by lesbian couples. Reforms in the United Kingdom’s Human Embryology and Fertilisation Act 2008 and the Canadian province of Quebec’s civil code are compared with empirical work from the social sciences on lesbians’ family practices. The reflective claim rests on problematic ideas about social practices and law. Since law is always blunt and incomplete, choices must be made as to which practices it should aim to recognize. Furthermore, the impact of heterosexist and homophobic conditions on lesbian families means that observable practices may not be a suitable model for gay-affirmative reforms. As advanced in the literature, the reflective claim overlooks law and society’s complex interaction, including how reform will not merely reflect but also alter practices. It fails to do justice to law reform’s normative character, obscuring its costs and positive potential
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; angleterre; approches et analyses; canada; corps; cours; discipline; discours dominant; droit; droit des femmes*; europe; hétérosexisme; identités LGBTQIA2+; inégalités; maternité; parentalité; premier cycle; périodes historiques; queer; québec; régions géographiques; science politique et droit; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques